Letter from the editor (2016)
At the end of the 2016 and early 2017, Earth Sciences Research Journal wants to thank you for making this project a successful journal. Four numbers in one year were our principal milestone for 2016. In total, we issued 44 papers expecting to sum our efforts in the Earth Sciences' state of the art. Comparing to recent years, we have increased our figures in publishing and citation close to the 200 percent. For 2017, the commitment is the same: hard-working for the best of your papers and the journal. As part of our mission, we'd like to make a brief list of the highlighted events for 2017 around the world on geophysics and geology, as invitation letter to pay attention them. For March is scheduled in Cyprus the Fifth International Conference on Remote Sensing and Geo-Information of the Environment. The conference sessions and workshops include presentations regarding the state-of-the-art methods and innovative projects in various areas of remote sensing and geoinformation. One of the most important meetings in the field will be celebrated in April, the Association of Petroleum Geologists Annual Convention and Exhibition 2017, in Houston. The AAPG is positioned to attract a focused audience of geoscience professionals. The event has an average of 6900 global attendees from 78 countries over the las five years, according to organizers reports. Same on April is scheduled the European Geoscience Union (EGU) General Assembly, in Viena, Austria. The EGU aims to provide a forum where scientists, especially early career researchers, can present their work and discuss their ideas with experts in all fields of geoscience.In Calgary, Canada, between 15 and 19 May 2017, will take place the GeoConvention. The event expects going beyond the traditional technical sessions, GeoConvention 2017 will take a holistic approach to a vast spectrum of topics including financial market and long-term strategy, infrastructures, regulations, safety and environmental protection, among others.For those how are students with innovation ideas, Paris will be the host of the European Association of Geoscientists and Engineers 79 Conference, Student Programme. Organizers are expecting 6000 experts attending, more than 1000 presentations in facilities over the 11.000 square meters.For September 2017, in Australia, will be held the 18th Annual Conference of International Association for Mathematical Geosciences. The meeting will provide a venue for the presentation of research and developments in mathematical geosciences in the form of oral and poster presentations, in the historic port city of Fremantle in Western Australia.In October is expected the joint meeting of the International Sedimentological Association (IAS) and the Association des Sédimentologistes Français (ASF). This event will bring the opportunity to gather the sedimentological and associated geological research communities to share experiences, to discuss new challenges, and to stimulate future rewarding collaborations.In Turkey, a country from many papers are coming from to Earth Sciences Research Journal, will celebrate the Fourth International Conference on Earthquake Engineering and Seismology, on October. The principal aim of the conference is to bring all national and international researchers within the earthquake engineering and seismology disciplines together and to facilitate their participation in a scientific environment.In this same month will be celebrated the American Association of Petroleum Geologists International Conference and Exhibition 2017, in London, and The Geological Society of America (GSA) 2017 Annual Meeting, in Seattle, the United States.We hope all this information is usable for you and expect the papers we are presenting can attract your attention. Our next volume will be ready soon!